Azaphosphatrane Organocatalysts in Confined Space: Cage Effect in CO2 Conversion. Issue 28 (30th May 2014) - Chatelet, Bastien; Joucla, Lionel; Dutasta, Jean‐Pierre; Martinez, Alexandre; Dufaud, Véronique
Abstract The endohedral functionalization of a molecular cage by an azaphosphatrane unit has allowed for the creation of highly engineered catalytic cavities for efficient conversion of CO2 into cyclic carbonates. Strong structure/activity/stability correlations have been demonstrated by careful adjustment of the size, shape, and electronic properties of the hemicryptophane host.